High-intensity interval training has positive effects on performance In ice hockey players - Naimo, M. A.; de Souza, E. O.; Wilson, J. M.; Carpenter, A. L.; Gilchrist, P.; Lowery, R. P.; Averbuch, B.; White, T. M.; Joy, J. (International Journal of Sports Medicine, 2015)
In spite of the well-known benefits that have been shown, few studies have looked at the practical applications of high-intensity interval training (HIIT) on athletic performance. This study investigated the effects of a HIIT program compared to traditional continuous endurance exercise training. 24 hockey players were randomly assigned to either a continuous or high-intensity interval group during a 4-week training program. The interval group (IG) was involved in a periodized HIIT program. The continuous group (CG) performed moderate intensity cycling for 45-60 min at an intensity that was 65% of their calculated heart rate reserve. Body composition, muscle thickness, anaerobic power, and on-ice measures were assessed pre- and post-training. Muscle thickness was significantly greater in IG (p=0.01) when compared to CG. The IG had greater values for both delta peak power (p<0.003) and delta mean power (p<0.02). Additionally, IG demonstrated a faster delta sprint (p<0.02) and a trend (p=0.08) for faster delta endurance test time to completion for IG. These results indicate that hockey players may utilize short-term HIIT to elicit positive effects in muscle thickness, power and on-ice performance.